2019
DOI: 10.1016/j.rmcr.2019.100850
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous lipid pneumonia in old people caused by aspiration: Two case reports and literature review

Abstract: Background Exogenous lipoid pneumonia is a rare entity, the diagnosis is often missed or delayed. Objective To investigate the clinical characteristics of exogenous lipid pneumonia in elderly patients, improve the efficiency of early diagnosis and treatment of this disease. Methods Retrospectively analyzed the clinical information and imaging data of these 2 exogenous lipid pneumonia patients, reviewed related literature. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…It has been established that inhaling various oils and high-molecular-mass lipophilic compounds causes this condition. Repeated or extended inhalation and pulmonary exposure to substances including mineral oil, squalene, Vaseline, olive oil, castor oil, omega-3-acid esters, rendered animal fat, and amiodarone are known to cause lipoid pneumonia [33][34][35][36][37][38][39]. Given that VEA is also a high-molecular-mass, semi-volatile and lipophilic oil with similar chemical and physical properties (logP oct/water >6 and boiling point >200 • C at 760 mmHg) as compounds that are known cause lipoid pneumonia, it is possible that VEA is causative or contributes to the development of EVALI and lipoid pneumonia.…”
Section: Vaping and Pulmonary Diseasementioning
confidence: 99%
“…It has been established that inhaling various oils and high-molecular-mass lipophilic compounds causes this condition. Repeated or extended inhalation and pulmonary exposure to substances including mineral oil, squalene, Vaseline, olive oil, castor oil, omega-3-acid esters, rendered animal fat, and amiodarone are known to cause lipoid pneumonia [33][34][35][36][37][38][39]. Given that VEA is also a high-molecular-mass, semi-volatile and lipophilic oil with similar chemical and physical properties (logP oct/water >6 and boiling point >200 • C at 760 mmHg) as compounds that are known cause lipoid pneumonia, it is possible that VEA is causative or contributes to the development of EVALI and lipoid pneumonia.…”
Section: Vaping and Pulmonary Diseasementioning
confidence: 99%
“…The clinical manifestations of ELP are atypical and similar to those of other types of pneumonia, making it easy to misdiagnose. Additionally, they are a function of the type and amount of inhaled oily substance [ 10 ]. Betancourt et al [ 11 ] reported that ELP could be divided into acute and chronic forms.…”
Section: Discussionmentioning
confidence: 99%
“…This notion has prompted clinicians to perform whole lung lavage and repeated BAL to eliminate the foreign material, 5,[25][26][27][28] to prescribe immunosuppressants, namely corticosteroids, to mitigate the body's inflammatory response, or both. 5,25,29,30 Clinical and radiologic deterioration occurred in nearly two-fifths of the cohort (38% and 39%, respectively).…”
Section: Discussionmentioning
confidence: 99%